Karakteristik Sabun Padat Pada Perlakuan Penambahan Penstabil Tween 80 - Viani, Sofia Charlotie; Putranti, Jessica Ayuningtyas; Jelau, Kaprianto (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
The research conducted sought to determine the impact of the addition and amount of tween 80 to obtain the best solid soap characteristics. This research is a one-factor experimental study, namely the percentage of tween 80 addition (0%, 0.25%, 0.5%, 0.75%, and 1%). The results showed that the addition of tween 80 had a significant effect on the hardness, pH, foam, moisture, firmness, brightness (L*), and yellowness (b*) of solid soap, but had no significant effect on redness (a*) and foam stability. Increasing the level of tween in the mixture will cause the moisture of the foam to increase, resulting in a firmer, higher pH, brighter and more yellow color intensity. The conclusion based on the data encountered by the author is that the solid soap added with tween 80 as much as 0.75% has the best characteristics, referring to the physicochemical data which shows the results of foam with a pH of 10.45 ± 0.49, foam stability of 85.67 ± 3.30, texture of 22.38 ± 0.70, level of brightness (L*) 86.35 ± 0.354, level of redness (a*) 0.95 ± 0.636, and level of yellowness (b*) 2.7 ± 0.141. As for the organoleptic test (scoring and hedonic), panelists prefer soap with the treatment of adding 1% tween 80 showing the highest value, namely the foam is rated 4.75 ± 0.44, the stickiness is 4.45 ± 0.89, the humidity is 4.45 ± 0.69, and the overall acceptance is 5.95 ± 0.83.